The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4103/0972-0707.97964
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the antimicrobial activity of natural extracts of Morinda citrifolia, papain and aloe vera (all in gel formulation), 2% chlorhexidine gel and calcium hydroxide, against Enterococcus faecalis: An in vitro study

Abstract: Aim:A comparative evaluation of the antimicrobial activity of natural extracts of Morinda citrifolia, papain, and aloe vera (all in gel formulations), 2% chlorhexidine gel and calcium hydroxide, against Enterococcus faecalis—an in vitro study.Materials and Methods:The antimicrobial efficacy was assessed in vitro using dentin shavings collected at 2 depths of 200 and 400 μm. The total colony forming units at the end of 1, 3, and 5 days were assessed.Results:The overall percentage inhibition of bacterial growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 20 publications
4
58
1
Order By: Relevance
“…Although bactericidal activity of papain has been reported for gram-positive and gram-negative organisms (Dawkins et al, 2003;Chukwuemeka, Anthoni, 2010;Bhardwaj, Ballal, Velmurugan, 2012), there is no consensus about this function. Ferreira et al (2008) Considering the proteolytic characteristic described for papain and the biopolymer matrix composition of bacterial biofilms, this study aimed to evaluate the ability of papain to act as an inhibitor of biofilms in different concentrations.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although bactericidal activity of papain has been reported for gram-positive and gram-negative organisms (Dawkins et al, 2003;Chukwuemeka, Anthoni, 2010;Bhardwaj, Ballal, Velmurugan, 2012), there is no consensus about this function. Ferreira et al (2008) Considering the proteolytic characteristic described for papain and the biopolymer matrix composition of bacterial biofilms, this study aimed to evaluate the ability of papain to act as an inhibitor of biofilms in different concentrations.…”
Section: Introductionmentioning
confidence: 98%
“…Although bactericidal activity of papain has been reported for gram-positive and gram-negative organisms (Dawkins et al, 2003;Chukwuemeka, Anthoni, 2010;Bhardwaj, Ballal, Velmurugan, 2012), there is no consensus about this function. Ferreira et al (2008) found this activity for Staphylococcus aureus and Pseudomonas aeruginosa only in 10% of papain.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bhardwaj et al 19 evaluated the antimicrobial activity of three natural extracts and chlorhexidine 2%. They observed that chlorhexidine eliminated 100% of microorganisms, followed by the natural extracts.…”
Section: Antimicrobial Activitymentioning
confidence: 99%